Ethical issues identified by General Practitioners in private practice in the Johannesburg area as challenges to the successful implementation of the proposed National Health Insurance - Jacovides, Andrew (My University, 2017)
Introduction National Health Insurance (NHI) has been proposed in South Africa to ensure that everyone has access to appropriate, efficient and quality health services. Involving the private healthcare sector is essential for this to occur because of its resources. Significant changes to the private healthcare structure are anticipated for its incorporation into the NHI plan. This study examines the perceptions of General Practitioners (GPs) from the private sector in the Johannesburg area on the NHI. It examines the challenges they foresee that will impact on their willingness to participate in the NHI and how these might manifest as ethical concerns. These findings will yield effective ways these concerns are addressed with regard to their acceptance of the NHI and any ethical issues they may have regarding the effective delivery thereof. Study design The study took the form of an exploratory-descriptive empirical method using semi-structured interviews. Method The qualitative data was analysed using thematic content analyses. Results The general perception of the NHI by the General Practitioners was negative. The NHI was perceived by the doctors in this study to be an extension of the current public health sector. The current perception of the public health sector is one of inferior care; an over worked and understaffed facility; a poorly maintained system with inadequate supervision; and one that is rampant with corruption. The key ethical concerns arising from this study is the quality of care for the patients, basic working conditions in government facilities; corruption in, and a general mistrust of the government. Concerns were raised about quality of patient care in the public sector and the possibility of “downgrading” private health care. These factors impose on the patients’ right to dignity, equality and freedom as poor quality of health care infringes these rights. Conclusion and recommendations To gain “buy-in” from GPs, the establishment of trust, improved communication and an end to mismanagement and corruption are essential for the NHI to be successfully implemented.
Ethical issues identified by medical doctors in private practice in Johannesburg as challenges to the successful implementation of the proposed National Health Insurance
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in the field of Bioethics and Health Law. Johannesburg June 2017.
Keywords: National Health Insurance; General Practitioners